Currículo e transversalidade: um olhar sobre a nova legislação - SANTANA, Cintia Wanily Oliveira Mendes (2020)
Education as an indispensable factor for human development assumes a role of paramount importance in the life of all individuals. So, one wonders: What is the importance of discussing gender and sexuality in school education, in elementary school? Through this central problem of study, it was thought as a general objective to understand the importance of the discussion of the thematic gender and sexuality for the school, political and social formation. Among the bibliographical sources are the works of Marlucy Paraíso, Dagmar Meyer, Guacira Louro and Michel Foucault. As a methodology, the study was based on the post-critical perspective in education, thus, it started from clues and suspicions pointed out by related scholars, so that other ways of reflecting on the gross object could be given movement. The study concluded that the curriculum, facing the tensions that encompass life in society, cannot give up discussing about multiplicity, diversity and difference. However, we can see in the present times the silencing of diversity, the hiddenness of multiplicity and the exclusion of bodies and identities. It is understood that in a curriculum there are many movements that assume political or ideological character. Given this, the teacher education must lean towards the discovery of new spaces, spaces of resistance and dissension, proliferating the desire and will for power that drives the actions of the education professional. So that this desire can extend the limits of the curriculum, giving it light voice, movement, sexuality, gender and transversality